2008
DOI: 10.14310/horm.2002.1111039
|View full text |Cite
|
Sign up to set email alerts
|

Serum transforming growth factor-beta 1 levels in normoalbuminuric and normotensive patients with type 2 diabetes. Effect of metformin and rosiglitazone

Abstract: OBJECTIVE: a)To determine serum Transforming Growth Factor-beta 1 (TGF-β1) levels in patients with type 2 diabetes who do not have diabetes related complications and in healthy controls, b) to evaluate the effects of metformin and rosiglitazone on TGF-β1 levels. DESIGN: In the washout period, 61 patients with Fasting Plasma Glucose levels (FPG) higher than 140 mg/dl, Postprandial Glucose (PPG) levels higher than 180 mg/dl and A1c levels exceeding 6.5% were treated with glimperide. After 4 weeks, 39 of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
3
11
1
Order By: Relevance
“…Moreover, in vitro studies found that TGF-β1 is responsible for development of mouse β-cells, and this may be explain the increase of TGF-β1 in T2DM which result from increase insulin demand. Previously, several studies showed high TGF-β1 levels in T2DM (Yener et al, 2008). Present study is similar to previous studies which shows higher TGF-β1 level in T2DM.…”
Section: Results:-supporting
confidence: 92%
“…Moreover, in vitro studies found that TGF-β1 is responsible for development of mouse β-cells, and this may be explain the increase of TGF-β1 in T2DM which result from increase insulin demand. Previously, several studies showed high TGF-β1 levels in T2DM (Yener et al, 2008). Present study is similar to previous studies which shows higher TGF-β1 level in T2DM.…”
Section: Results:-supporting
confidence: 92%
“…While we infer that FFA signals promote autocrine TGF-β1 secretion from β-cells within the islets thus activating Smad3 signaling, we cannot exclude the possibility that other cells within the islets or within the pancreatic milieu serve as a paracrine source for TGF-β's actions. Indeed, circulating levels of TGF-β1 are increased in human T2D patients 58,59 and in HFD-fed mice 60 , thus allowing for the possibility of paracrine modes of activation of Smad3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ and TNF-␣ increase in the circulation of obese and diabetic humans (15,19,29,61,63), HFD-fed rodents (20,61), and STZ-diabetic rats (4,21,22). TGF-␤ promotes adiposity and glomerular pathology in obesity and diabetes, and both the adipose and renal tissues are major sources of TGF-␤ released into the circulation (14,22,23,61).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we investigated whether the production of PRL is downregulated in the AP of obese and diabetic rats and evaluated whether alterations in the AP expression of TGF-␤ and/or TNF-␣ correlated with these changes. TGF-␤ and TNF-␣ increase in the circulation of obese and diabetic patients (15,19,29,61,63) and play important roles in insulin resistance and diabetes pathophysiology (59,61). Also, these cytokines and their receptors are ubiquitously expressed in a variety of tissues from rodents and humans, including the AP PRL-producing cell (lactotrope) (17,65), where TGF-␤ inhibits (24,49) and TNF-␣ can stimulate (27,36), but also inhibit (30,58), PRL synthesis and release; however, there is little or no information regarding the actions of TNF-␣ or TGF-␤ on PRL secretion in the context of metabolic diseases.…”
mentioning
confidence: 99%